Metal–Organic Frameworks Encapsulated in Photocleavable Capsules for UV-Light Triggered Catalysis - Deleu, Willem P. R. (2015)
A smart catalyst that can be activated by UV-light was prepared by encapsulating Metal-Organic-Framework (MOF) particles in microcapsules with a photocleavable polyurea shell. Addition of palmitic acid as a modulator during the synthesis of the Fe-terephthalate MOF MIL-88B(Fe) yields MOF particles with a hydrophobic surface. These particles can be successfully encapsulated via interfacial polymerization, as proven by a combination of PXRD, SEM and EDX techniques. By the incorporation of photolabile groups in the polymer shell, UV light can be employed to trigger degradation of the capsules, releasing the catalytic load. Catalyst activation triggered by UV light was monitored by recording the rates for catalytic tetramethylbenzidine (TMB) oxidation with H2O2. The reactivity could be controlled by tuning irradiation time, UV intensity or MOF loading. The activity of the capsules was up to 90 times higher after irradiation.